Readings and cases in information security : law and ethics - Whitman, Michael E. (Boston, Massachusetts : Cengage Learning Asia Pte Ltd, 2011)
READINGS AND CASES IN INFORMATION SECURITY: LAW AND ETHICS provides a depth of content and analytical viewpoint not found in many other books. Designed for use with any Cengage Learning security text or as a standalone professional reference, this book offers readers a real-life view of information security management, including the ethical and legal issues associated with various on-the-job experiences. Included are a wide selection of foundational readings and scenarios from a variety of experts to give the reader the most realistic perspective of a career in information security.
1. Preface & Acknowledgments 2. Running case: stratified custom manufacturing -- 3. Personnel and privacy -- 4. Risk management -- 5. Management of security technology -- 6. Information security program management -- 7. Information security governance and regulatory compliance.
Includes index.
Keywords: COMPUTER NETWORKS -- MORAL AND ETHICAL ASPECTS